Can english language media connect with ethnic audiences?: Ethnic minorities’ media use and representation perceptions - La Ferle, Carrie and Lee, Wei-Na (Cambridge University Press, 2005)
"With the size of ethnic minority groups expanding and their disposable income increasing, the consumption landscape and media environment are constantly evolving. It is important for advertisers to understand how ethnic minority group members feel about being targeted by current multicultural marketing communication practices and if English language media for the general market are still a good way to reach these consumers. Past research has often employed a content analysis technique to gauge instances of ethnic minority representation in advertising. However, a void exists in the literature with respect to examining how ethnic minorities actually feel about tactics and messages directed at them. Therefore a cross-cultural survey of adults in three ethnic groups in the United States was carried out to examine these attitudes and also to assess current media use patterns. The results suggest that English broadcast media are still a good way to reach people across the various groups. The study further reveals that attitudes toward the frequency and accuracy of these groups as portrayed in advertisements are somewhat different from the negative viewpoints historically found in the literature. In fact, the results suggest that todays advertisements are not considered inadequate or inaccurate by many and that efforts toward targeting ethnic minorities are potentially welcomed. However, a bi-modal distribution across several representation issues indicates that advertisers must still be cautious in the minds of some ethnic minority consumers. Implications for advertisers and media planners are discussed as well as suggestions for future research." [Information des Anbieters]
https://katalog.adlr.link/Record/finc-80-8509